Susceptibility of Enterococcus faecalis and Lactobacillus casei strains isolated from palmita-type venezuelan cheese to bacteriophages - Cabrera, Lilibeth; Ferrer, Alexis; Ojeda de Rodríguez, Graciela (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Ten fresh cheese whey samples from local plants were analyzed to detect bacteriophages and evaluate the phage effects on the titratable acidity production in 10% sterile skim milk of eleven Enterococcus faecalis and seven Lactobacillus casei strains, which can be used as starters for the manufacture of Palmita-type Venezuelan cheese. The results showed that four whey samples were positive for phages, with lytic activity demonstrated by the presence of plaques from 0.2 to 0.3 mm in diameter on both M17 and MRS agar plates. The fermentative activity tests showed that 91% of the cultures with E. faecalis strains and 57% with L. casei strains were resistant to the isolated phages. Variations were observed between species as well as between strains of the same species. Such variability suggests the use of strains resistant to bacteriophages in order to guarantee the cheese quality.